Nature based solutions for removal of steroid estrogens in wastewater - Liyanage, Sureka; Lay, Mark; Glasgow, Graeme; Tanner, Chris; Craggs, Rupert; Northcott, Grant (Frontiers in Microbiology, 2024)
Estrogens are a growing problem in wastewater discharges because they are continuously entering the environment and are biologically active at extremely low concentrations. Their effects on wildlife were first identified several decades before, but the environmental limits and the remedial measures are still not completely elucidated. Most conventional treatment processes were not designed with sufficiently long retention times to effectively remove estrogens. Nature-based wastewater treatment technologies such as treatment wetlands (TW) and high-rate algal ponds (HRAP) are economically feasible alternatives for decentralized wastewater treatment and have promise for removing steroid hormones including estrogens.For small communities with populations below 50,000, the overall cost of TWs and HRAPs is considerably lower than that of advanced decentralized treatment technologies such as activated sludge systems (AS) and sequencing batch reactors (SBR). This results from the simplicity of design, use of less materials in construction, lower energy use, operation and maintenance costs, and operation by non-skilled personnel. The nature-based technologies show high removal (>80%) for both natural and synthetic estrogens. Estrogen removal in TWs can be enhanced using alternative media such as palm mulch, biochar, and construction wastes such as bricks, instead of traditional substrates such as sand and gravel. While TWs are effective in estrogen removal, they have the disadvantage of requiring a relatively large footprint, but this can be reduced by using intensified multilayer wetland filters (IMWF). Using filamentous algae in HRAP (high-rate filamentous algal pond; HRFAP) is an emerging technology for wastewater treatment. The algae supply oxygen via photosynthesis and assimilate nutrients into readily harvestable filamentous algal biomass. Diurnal fluctuations in oxygen supply and pH in these systems provide conditions conducive to the breakdown of estrogens and a wide range of other emerging contaminants. The performance of these naturebased systems varies with seasonal changes in environmental conditions (particularly temperature and solar irradiation), however a greater understanding of operating conditions such as loading rate, hydraulic retention time (HRT), pond/bed depth, dissolved oxygen (DO) concentration and pH, which influence the removal mechanisms (biodegradation, sorption and photodegradation) enable TWs and HRAPs to be successfully used for removing estrogens.